TAKTIC: A prospective, multicentre, uncontrolled, phase IB/II study of LY2780301, a p70S6K/AKT inhibitor, in combination with weekly paclitaxel in HER2-negative advanced breast cancer patients. (December 2021) - Vicier, Cecile; Sfumato, Patrick; Isambert, Nicolas; Dalenc, Florence; Robert, Marie; Levy, Christelle; Rezai, Keyvan; Provansal, Magali; Adélaïde, José; Garnier, Séverine; Guille, Arnaud; Carbuccia, Nadine; et al.
Abstract: Background: Hormone-resistant HER2-negative or triple-negative advanced breast cancers (ABC) are routinely treated with paclitaxel chemotherapy. LY2780301 is a dual inhibitor of p70 ribosomal protein S6 kinase and AKT. The TAKTIC study aimed at exploring the combination of paclitaxel and LY2780301 in this population. Methods: In this multicentric phase Ib/II trial, we enrolled patients with HER2-negative ABC, with (phase IB) or without (phase II) prior to cytotoxic treatment for advanced disease. Oral LY2780301 was administered once daily in combination with intravenous weekly paclitaxel. Primary endpoints were to determine the recommended phase II dose (RP2D) of the combination of LY2780301 with weekly paclitaxel (phase Ib), and to estimate a 6 months objective response rate (ORR) (phase II) in patients with HER2-negative ABC, both in the overall patient population and in cases with activation of the PI3K/AKT pathway (PI3KAKT+). Results: A total of 51 patients were enrolled; RP2D was LY2780301 500 mg QD+ paclitaxel 80 mg/m 2 . Main drug-related adverse events noted in phase Ib included neuropathy (75% of patients, grade 3–4 in 8%), asthenia (58% of patients, no grade 3–4), and ungual toxicity (50% of patients, grade 3–4 in 25%). They were similar in the phase II part, except that 14% of patients experienced pneumonia (grade 3–4 in 6%). In the phase II part, 6-month ORR in the overall population and in PI3KAKT+ subgroup were, respectively, 63.9% [48.8–76.8] and 55% [35–73.7]. Conclusion: Combining LY2780301 and weekly paclitaxel in patients with HER2-negative ABC was feasible with preliminary evidence of efficacy in both the overall population and the PI3KAKT+ subgroup. Trial registration id: NCT01980277 . Highlights: LY2780301 (LY) is a dual AKT/S6 inhibitor. This phase I/II trial aimed to evaluate LY in combo with weekly paclitaxel in HER2− ABC. Combining LY2780301 + weekly paclitaxel was feasible and safe. Antitumour activity was observed independently of PI3K/AKT pathway activation.